MULTILEVEL OSTEOSYNTHESIS OF THE LOWER EXTREMITIES BY THE ILIZAROV METHOD TO ELIMINATE DEFORMITIES AND SHORTENINGS IN CHILDREN AND ADOLESCENTS - Jahongirovna Mahlie Jumayeva (Journal of Medical Genetics and Clinical Biology, 2024)
-